Cronologia vieții literare românești (1993–1996): romanul Moromeţii - Bianca Burța-Cernat; Lucian Chișu; Oana Soare; Paul Cernat; Andrei Milca; Ion Oprișan (Revista de Istorie și Teorie Literară)
We hereby present comments referring to Marin Preda and his work, mainly regarding his novel The Moromete Family, as sixty years are celebrated from its publishing, using excerpts of the four volumes of the Romanian Literary Chronology – the Post-Communist Period, coordinator Eugen Simion, the Publishing House of the National Museum of Romanian Literature, 2015 (under printing). A group of researchers up of Bianca Burța-Cernat (publishing coordinator), Lucian Chișu, Oana Soare, Paul Cernat, Andrei Milca and Ion Oprișan participated in the preparation and elaboration of the documentary material.